Visual Imagery Strategy In Enchance Students’ Reading Comprehension - T, Syamsu; Hermansyah, Sam (La Ogi : English Language Journal, 2021)
The objective of the research were to find out whether or not the use of Visual Imagery Strategy can enhance the students’ reading comprehension at the Eighthof MTs Pondok Pesantren Al-Urwatul Wutsqa Benteng.This research employed a quantitative method that applied one class. The population of this research was the eighth grade students in academic year 2019-2020. There were 253 students spread in eighth classes (VIII.A, VIII.B,VIII.C, VIII.D, VIII.E, VIII.F, VIII.G, and VIII.H) and each class consist appropriately 27-37 students. The researcher took simple random and chose VIII.C as the representative and the number of total sample is 23 students.The data of the research were collected by using one kinds of instruments, namely reading comprehension test. Reading test was used to obtain data of the students’ reading comprehension ability in Reading Comprehension by using visual Imagery strategy.The result of data analysis showed that there was significant difference between the students’ score after they were taught by using Visual Imagery Strategy and before they were taught by Visual Imagery Strategy. It was proved by the mean score of the post-test which was higher than the mean score of pre-test (62.04>53.86). Furthermore, the result of the p-value (0.004) was lower than level of significant (α = 0.05); which means that H1 was accepted. Based on data analysis, the research concluded that: the use of Visual Imagery Strategy effective in improves students’ reading comprehension.